EFFECT OF ADDITION OF DEXAMETHASONE TO ROPIVACAINE ON POST-OPERATIVE ANALGESIA IN ULTRASOUND-GUIDED TRANSVERSE ABDOMINIS PLANE BLOCK FOR ANTERIOR ABDOMINAL WALL HERNIA REPAIR - GARHWAL, POOJA; PARASHAR, SHOBHA; MITHARWAL, SANWAR MAL; VIJAY, POOJA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the present study was to evaluate the adjuvant effect of dexamethasone to Ropivacaine in ultrasound-guided transverse abdominal plan block for anterior abdominal wall hernia repair. Methods: A single-blind randomized control trial was conducted by selecting patients undergoing anterior abdominal wall hernia and dividing them into two groups with Group A: received a total of 50 mL of 0.2% Ropivacaine (48 mL) with normal saline (2 mL) and Group B received a total 50 mL of 0.2% Ropivacaine (48 mL) with 8 mg dexamethasone (2 mL). Outcome was assessed on the basis of visual analog scale (VAS), the requirement of rescue analgesia, and adverse events. Results: Twenty-seven patients were recruited in each group, Group A and Group B had an average pain-free interval of 11.85±2.82 and 8.07±2.51, respectively (p<0.001). Mean VAS was lower in Group B at the end of 2 h (p<0.05). Both the groups had similar side effects with no significant difference. Total analgesia dose required in Groups B and A was 75 and 96 mg, respectively (p<0.001). Conclusion: A combination of 0.2% Ropivacaine (48 mL) with 8 mg dexamethasone (2 mL) significantly reduces the VAS in post-operative pain along with reduced quantity and frequency of rescue analgesia.